Translation and postcolonialities: transactions across languages and cultures - Vijaya Guttal (ed.); Suchitra Mathur( ed.) (New Delhi : Orient Blackswan, 2013)
Papers presented at the international conference on "Translation and Postcolonialities", held at Dharwad during 16-18 February 2009.
Keywords: Postcolonialism; Language and Culture; Translation Studies; Languages